Quantal response equilibria for posted offer-markets - López Acevedo, Gladys (Estudios Económicos de El Colegio de México, 1997)
There is a growing body of data from game theory and industrial organization experiments that reveals systematic deviations from Nash equilibrium behavior. In this paper, the perfectly rational decision-making embodied in Bertrand-Nash equilibrium is generalized to allow for endogenously determined decision errors. Closed-form solutions for equilibrium price distributions with endogenous errors are derived for several different models. In some of these models, the price distribution in a quantal response equilibrium, QRE, is affected by changes in structural variables although the Nash equilibrium remains unaltered. The quantal response approach is appealing since it thereby accounts for systematic deviations from the Bertrand-Nash equilibrium.